Allergic Rhinitis and its Impact on Asthma (ARIA): Achievements in 10 years and future needs - (:unkn) unknown (MOSBY-ELSEVIER, 2012)
Allergic rhinitis (AR) and asthma represent global health problems for all age groups. Asthma and rhinitis frequently coexist in the same subjects. Allergic Rhinitis and its Impact on Asthma (ARIA) was initiated during a World Health Organization workshop in 1999 (published in 2001). ARIA has reclassified ARas mild/moderate-severe and intermittent/persistent. This classification closely reflects patients' needs and underlines the close relationship between rhinitis and asthma. Patients, clinicians, and other health care professionals are confronted with various treatment choices for the management of AR. This contributes to considerable variation in clinical practice, and worldwide, patients, clinicians, and other health care professionals are faced with uncertainty about the relative merits and downsides of the various treatment options. In its 2010 Revision, ARIA developed clinical practice guidelines for the management of AR and asthma comorbidities based on the Grading of Recommendation, Assessment, Development and Evaluation (GRADE) system. ARIA is disseminated and implemented in more than 50 countries of the world. Ten years after the publication of the ARIAWorld Health Organization workshop report, it is important to make a summary of its achievements and identify the still unmet clinical, research, and implementation needs to strengthen the 2011 European Union Priority on allergy and asthma in children. (J Allergy Clin Immunol 2012;130:1049-62.)
Keywords: Rhinitis; asthma; Allergic Rhinitis and its Impact on Asthma; allergy; GRADE; QUALITY-OF-LIFE; WORLD-HEALTH-ORGANIZATION; UPDATE; CLASSIFICATION; VALIDATION; GUIDELINES; MANAGEMENT; COLLABORATION; INTERMITTENT; PREVALENCE